Penggunaan Perangkat Pembelajaran Biologi pada Sekolah Menengah Atas Negeri Kabupaten Simeulue - Hendry Ismomon (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
Material resources are a number of materials, tools, media, instructions and guidelines used by the teacher in the learning process. Material resources in teaching and learning procces can be: the syllabus, RPP, the material taught, LKPD, media and assessment of learning. The use material resources of biology still can not be adjusted to the implementation of learning and is not used fully by the teacher. Formulation of the problem in this research is how to use the material resources of learning biology in SMA Negeri Simeulue. The goal is to determine the use of biological material resources.This research is a survey research with a qualitative descriptive approach. The number of respondents in this study as many as 22 people. The collection of data in this study done by observation in the classroom after teachers taught, researchers give the question form which contains a number of questions about the use of biological material resources.The results showed the use of the material resources syllabus as much 95,45%, biology teacher use material resources and RPP as much around 86.36%, using LKPD many as 59,09%, to use learning media as much as 68.18% and as much 81.81% the teachers make the learning assessment.It was concluded that in general biology teacher in SMA Negeri Simeulue has been prepared completeness the material resources of biology, using material resources determine the RPP and teaching materials in accordance with the curriculum, some biology teacher using LKPD based on RPP, but only a small part of biology teacher use LKPD each semester. Most of the biology teacher use learning media and learning assessment, but only a fraction of the biology teacher who do experiments in the laboratory and drafting plans for remedial. Recommended that the biology teacher to use maximum of material resources, such as the use of LKPD on every semester, do practical and drafting plans for remedial.